Designing multi-actor implementation: A mechanism-based approach. (January 2018) - Busetti, Simone; Dente, Bruno
The article offers analytical tools for designing multi-actor implementation processes. It does so by proposing a design approach centred on causal mechanisms. Such design strategy requires designers to focus primarily on causal theories explaining why implementers commit overtime to implementing policies. The central proposal is that design procedures should be reversed, i.e. start by reasoning on the causal mechanisms explaining implementers' behaviour and then go looking for design features. Several advantages of this approach related to designing, reforming, or transferring successful practices are discussed throughout the article. Finally, the article provides six extended examples of such mechanisms in different policy fields: actor's certification, blame avoidance, earning brownie points, repeated interactions, focusing events and attribution of opportunity or threat.